2020
DOI: 10.35808/ersj/1545
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Activity-Based Costing Approach for SMEs: The Case Study of an Italian Small Road Company

Abstract: Purpose:The paper proposes an original conceptual model for designing a simplified Activity-Based Costing (ABC) approach for Small and Medium-sized Enterprises (SMEs) by focusing on the transport sector. Design/Methodology/Approach: The model is designed starting from the distinctive characteristics of the SMEs' collaborative culture. The approach is then tested in the case of an Italian small-road company. Findings: The simplified ABC, which was gradually introduced in the SME, allowed the firm to gain confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…For this reason, we believe that, first of all, cost allocation systems, able to balance the cost of errors and measurements with the lower complexity of small and medium enterprises (Cooper and Kaplan, 1998; Needy et al , 2003; Raucci and Lepore, 2020), can be a useful solution to support decision-making and pricing mechanisms, especially when matched with PSM. In small and medium-sized restaurants some simplified approaches of ABC for small and medium enterprises, tested already in other sectors, can be extended to facilitate their implementation.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason, we believe that, first of all, cost allocation systems, able to balance the cost of errors and measurements with the lower complexity of small and medium enterprises (Cooper and Kaplan, 1998; Needy et al , 2003; Raucci and Lepore, 2020), can be a useful solution to support decision-making and pricing mechanisms, especially when matched with PSM. In small and medium-sized restaurants some simplified approaches of ABC for small and medium enterprises, tested already in other sectors, can be extended to facilitate their implementation.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In small and medium-sized restaurants some simplified approaches of ABC for small and medium enterprises, tested already in other sectors, can be extended to facilitate their implementation. Suggested approaches are based on exploiting informal processes of behavioural control (Kocakulah et al , 2017; Raucci and Lepore, 2020), others suggest a low-weight ABC model for calculating costs (Roztocki et al , 2004) especially taking advantage of technology (Finke and Bušinska, 2011). In this perspective of simplification, the suggested costing system for the restaurant can take into account the whole organization as a single activity center, as also proposed by Annaraud et al (2008).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The research also revealed that MAPs have a strong correlation with firm performance. Increased adoption of MAPs has a positive impact on the financial performance of an organization, so organizations seeking to create and maintain a competitive advantage should increase their use of MAPs [58].…”
Section: Management Accountancy Techniques In Developing Nationsmentioning
confidence: 99%